FUTURE SOCIAL MEDIA MARKETING TRENDS IN THE ERA OF INSDUSTRIAL SOCIETY - Dony Martias (Adisam Publisher, 2024)
Social media is an effective way to market products and services widely which can increase sales and advance business. Social media still has a lot to offer in facilitating communication between businesses and their customers for the purpose of providing better service. The presence of social media continues to grow along with technological developments. Currently, social media is not only a space for communication, but also for self-expression and a means of promotion. This is because most people's lives are connected to social media. The future of social media in marketing is exciting, but also uncertain. It is important to consider the future of social media in the context of consumer behavior and marketing, as social media has become a vital marketing and communications channel for businesses, organizations and institutions, including those in the political field. Social media as technology is, centric but not entirely technological, an ecosystem in which a diverse and complex set of behaviors, interactions and exchanges involving many different types of actors are interconnected.